Primary immunodeficiencies, autoimmune hyperthyroidism, coeliac disease and systemic lupus erythematosus in childhood immune thrombocytopenia. (13th October 2020) - Saettini, Francesco; Cattoni, Alessandro; Redaelli, Martina; Silvestri, Daniela; Ferrari, Giulia Maria; Biondi, Andrea; Jankovic, Momcilo; Spinelli, Marco
Abstract: Aim: To evaluate the cumulative prevalence of coeliac disease, systemic lupus erythematosus, autoimmune hyperthyroidism and primary immunodeficiencies in children with either newly diagnosed/persistent or chronic immune thrombocytopenia (ITP). Methods: Monocentric retrospective analysis of the clinical and biochemical features of 330 consecutive patients with ITP referred to our Pediatric Hematology Unit between January 2009 and December 2018. Results: The prevalence of systemic lupus erythematosus (0.3%), coeliac disease (0.3%) and autoimmune hyperthyroidism (0.6%) was not increased compared to general paediatric population. Of note, the prevalence of underlying primary immunodeficiencies was 2.4%, remarkably higher than the general paediatric population ( P =  .005). All the patients diagnosed with immunodeficiency developed either bi‐/trilinear cytopenia or splenomegaly. Conclusion: Whilst autoimmune and immunological screening is already recommended at the onset of immune thrombocytopenia, we recommend that primary immunodeficiencies be regularly screened during follow‐up, especially in case of additional cytopenia or lymphoproliferation.